Association of parity and age at menarche with molecular subtypes of invasive breast cancer - Resti Arania; Amirah Zhafira Rizqiyanda; Zaleha Ulfa; Wien Wiratmoko (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Breast cancer is the most frequently diagnosed malignancy among women worldwide and remains a major public health concern. Reproductive factors, including parity and age at menarche, influence cumulative lifetime estrogen exposure and may contribute to the biological characteristics of breast cancer. However, evidence regarding their association with molecular subtypes of invasive breast cancer remains limited, particularly in Indonesia. Purpose: To determine the association between parity and age at menarche with the molecular subtypes of invasive breast cancer among patients treated. Methods: This analytic observational study employed a cross-sectional design using secondary data from medical records of 125 patients diagnosed with invasive breast cancer in 2025. Participants were selected using random sampling based on predefined inclusion and exclusion criteria. The independent variables were parity and age at menarche, while the dependent variable was the molecular subtype of invasive breast cancer determined by immunohistochemistry. Univariate analysis was used to describe participant characteristics, and bivariate analysis was performed using the Chi-square test. The strength of the associations was measured using Odds Ratios (ORs) with 95% confidence intervals (CIs). Statistical significance was established at p<0.05. Results: Most participants had a normal-to-late age at menarche (60.0%) and were multiparous or grand multiparous (52.0%). Luminal B was the predominant molecular subtype (32.0%), followed by Luminal A (27.2%), HER2 (22.4%), and Triple-Negative (18.4%). A significant association was observed between parity and molecular subtype (p=0.003; OR=0.282; 95% CI=0.119–0.672). Age at menarche was also significantly associated with molecular subtype (p=0.002; OR=0.229; 95% CI=0.087–0.606). Women with early menarche and nulliparity or primiparity were more likely to present with non-Luminal A molecular subtypes. Conclusion: Parity and age at menarche were significantly associated with the molecular subtypes of invasive breast cancer. Early menarche and low parity were more frequently associated with aggressive non-Luminal A molecular subtypes, highlighting the importance of reproductive history in breast cancer risk assessment and individualized management.